The Relationship between CEO Narcissism and Earnings Management: Evidence from Egypt - Elsharkawi, Elsaid (The Arab Journal of Administration, 2023)
This study aims to investigate the relationship between CEO narcissism and Earnings Management, both Real and Accrual-Based Earnings Management. Study period spanned from 2018 to 2019 and our sample consisted of 110 companies from Egyptian Stock Exchange Market (with 220 observations). Results indicate a negative relationship between CEO narcissism (measured by CEO’s signature size) and Real Earnings management. While the results illustrate that there is no relationship between CEO narcissism and Accrual-based Earnings management which is in accordance with the findings of (Olsen et al., 2013). This may be due to the fact that the CEO, including narcissist CEO, identifies himself with the company (Boivie et al., 2011), between his reputation and the reputation of the company; which makes him less inclined to engage in practices that may harm this reputation and his image before others. The lack of a relationship could also be due to the quality of auditing and governance in the companies; making it nearly impossible for a CEO to manage earnings on the basis of his narcissism.